Inhibition of wheat growth planted after glyphosate application to weeds. Issue 4 (4th July 2020) - Jang, Se Ji; Mallory-Smith, Carol; Kuk, Yong In
Abstract: Glyphosate is easily translocated from shoots to roots and released into the rhizosphere. The objective of this study was to clarify the influence of glyphosate residues in the root tissue of glyphosate-treated weeds on wheat ( Triticum aestivum L.) growth and shikimate accumulation. Foliar application to 5-leaf downy brome ( Bromus tectorum L.) planted in sandy loam soil reduced wheat ('Tubbs 06') shoot fresh weight by 37% to 46% compared with the control when seeds were planted 0 and 1 d after applications. With Italian ryegrass [ Lolium perenne L. ssp. multiflorum (Lam.) Husnot], wheat shoot fresh weight was inhibited by 20% to 34% compared with the control at 0, 1, 3, and 5 d after applications to 1.5- and 5-leaf-stage plants. Using a different wheat cultivar ('Stephens'), shoot fresh weight was inhibited by 19% to 43% when seeds were planted 0 d after glyphosate applications to 1.5-, 2-, and 5-leaf-stage B. tectorum and L. perenne planted in sandy loam soil compared with control. In contrast, some studies using treated L. perenne and B. tectorum planted in clay loam soil resulted in increases in wheat shoot fresh weight. Lolium perenne planted in water-saturated sandy loam soil showed no differences in either shoot or root fresh weight or shikimate accumulation in shoots or roots. Compared with the control plants, shikimate accumulation in roots increased 51- to 59-fold in wheat planted in sandy loam soil that previously contained B. tectorum and 13- to 49-fold in soil that previously contained L. perenne . In both studies, glyphosate was applied at the 1.5-leaf stage, and wheat seeds were sown 0, 1, and 3 d after glyphosate applications. Thus, plant damage caused by glyphosate was associated with increased shikimate accumulation in the root tissue. Overall, crop damage caused by glyphosate residue to target plants was strongly influenced by soil type, soil water conditions, glyphosate sensitivity, target weed species identity, and weed densities.